Has trade facilitation of the ‘Belt and Road’ countries promoted China's cross-border E-commerce exports? - Guo, Ping; Hamzah, Hanny Zurina; Chin, Lee (John Wiley and Sons Inc, 2024)
This paper investigates the impact of trade facilitation level on China's exports in cross-border e-commerce (CBEC) in 56 major ‘Belt and Road’ countries using PPML panel estimation. The total sample and sub-sample regressions based on the classification of developed and developing countries show that (1) the trade facilitation level of ‘Belt and Road’ countries has a significant positive impact on China's CBEC exports, but the impact of developed countries is greater than that of developing countries. (2) All five trade facilitation sub-indicators of the ‘Belt and Road’ countries have an impact on China's CBEC exports, but the impact of the logistics and e-commerce environments are prominent. (3) The impact of the customs environment of developed countries on China's CBEC exports is second only to that of the logistics environment, and the impact of the e-commerce environment in developing countries is greater than that of the logistics environment. To promote China's CBEC exports to the ‘Belt and Road’ countries, the Chinese government needs to prioritise cooperation in the logistics and e-commerce environments. In addition, cooperation with developed countries in particular needs to strengthen the customs environment construction, whilst cooperation with developing countries should prioritise the improvement of the e-commerce environment.